Integrating Occupational Safety and Health Management Systems (SMK3) with Total Quality Management (TQM) in Micro-Scale Manufacturing Enterprises - Sani Heronasia; Rida Zuraida (Science and Technology Research Centre Universitas PGRI Semarang, 2025)
Improving a company's Occupational Safety and Health Management System (SMK3) is key to achieving Total Quality Management (TQM) goals. This study uses questionnaires, fishbone diagrams, and Fault Tree Analysis to evaluate SMK3 implementation at a micro-scale manufacturing business, Malang Roster. The primary goal is to ensure work quality while maintaining a sustainable safety system. Findings show the most significant issues are low discipline in using personal protective equipment (PPE), poor supervision, and outdated equipment. Other challenges include inadequate health insurance planning and the use of subpar equipment. While safety signs are present, unauthorized access to hazardous areas remains a problem, requiring corrective action. To effectively integrate SMK3 into a TQM framework, companies must strengthen provisions, implementation, and monitoring. This study suggests that consistent supervision, targeted training, and structured audits are crucial for improving occupational safety in small manufacturing environments.